Ecological Niche Of Mugil Cephalus – An Ecopath With Ecosim Approach In Vellar Estuary (South East Coast Of India) - S.MURUGAN; ANTONY PUTHIYATH JOSEPH; S.AJMAL KHAN (International Journal of Pharma and Bio Sciences, 2012)
Steady-state Ecopath models were developed and used to compare production, biomass, consumption, biomass flows, and higher order indices of ecosystem functioning in Vellar estuary food web. The four seasons covered were Premonsoon, Monsoon, Postmonsoon and Summer. The estuarine ecopath model developed for Vellar estuary summarizes the total system throughput (biomass flows).It was found to be comparatively higher just like other estuarine ecosystems. Benthic carnivores, pelagic carnivores and sea bass are the top predators in the ecosystem; so the predation mortality was absent in these groups. Even though clupeids and shrimps contribute a major part of fisheries, the predation mortality in these groups was very high compared to fishing mortality. The reason behind this may be the high biomass of these groups in this estuarine ecosystem. Another reason may be possible higher predation on the larval and juvenile stages. The model does not account for the eggs and larval stages of the functional groups. Recruitment to the large groups of the model is therefore dependent on the sizes of the respective small groups, while the biomasses of the small groups are determined by the biomasses of the large groups. Ecopath with Ecosim (EwE) does not account for spatial issues such as overlap of potential predators and prey, a third component of the software, Ecospace, can account for (Christensen et al., 2000). The diet study showed that detritus can be an important component of mullet diet. Mullets utilize detritus and can thus function as a converter of energy into commercially exploitable species directly